Original papersComparison of anti-embolic protection with proximal balloon occlusion and filter devices during carotid artery stenting: clinical and procedural outcomes - TatlI, Ersan; Buturak, Ali; Grunduz, Yasemin; Dogan, Emir; Alkan, Mustafa; Sayın, Murat; Yilmaztepe, Mustafa; Atakay, Selcuk (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
Aim: The objective of this study was to compare the periprocedural and clinical outcomes after carotid artery stenting (CAS) with proximal protection devices versus with distal protection devices. Material and methods : Patients with internal carotid artery (ICA) stenosis undergoing CAS with cerebral embolic protection were randomly assigned to proximal balloon occlusion or distal filter protection. Adverse events were defined as death, major stroke, minor stroke, transient ischemic attack (TIA) and myocardial infarction (MI). Periprocedural and 30-day adverse events and ICA vasospasm rates were compared between the two embolic protection groups. Results : Eighty-eight consecutive patients were randomized: 48 patients with proximal protection (mean age 68.8 ±13.6, 66% male) and 40 patients with a distal protection device (mean age 65.4 ±12.3; 70% male). There was no significant difference in periprocedural or 30-day adverse event rates between the two groups (p > 0.05). However, there was a higher periprocedural ICA vasospasm rate in the distal filter protection group (9 patients, 23%) compared with the proximal balloon occlusion group (1 patient, 2%) (p = 0.019). Conclusions: There was no difference between the clinical periprocedural and 30-day adverse event rates of distal filter and proximal balloon protection systems. However, distal filter protection systems showed higher rates of periprocedural ICA vasospasm.